2020
DOI: 10.3390/v12050518
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Virus Like Particles (VLPs): Opportunities for H7N9 Vaccine Development

Abstract: In the midst of the ongoing COVID-19 coronavirus pandemic, influenza virus remains a major threat to public health due to its potential to cause epidemics and pandemics with significant human mortality. Cases of H7N9 human infections emerged in eastern China in 2013 and immediately raised pandemic concerns as historically, pandemics were caused by the introduction of new subtypes into immunologically naïve human populations. Highly pathogenic H7N9 cases with severe disease were reported recently, indicating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 118 publications
0
22
0
Order By: Relevance
“…Development of vaccines against SARS-CoV-2 is the priority in many pharmaceutical companies and academic organizations all over the world. A variety of SARS-CoV-2 vaccines, such as protein subunit 12 , replicating or non-replicating viral vector 13-15 , inactivated virus 16 , live attenuated virus 17-18 , virus-like particle (VLP) 19-20 , RNA- 21-22 or DNA-based 6, 23-24 vaccines, are currently under development. DNA vaccines have several advantages compared to traditional vaccines, such as protein subunits, peptides, and living/inactivated pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Development of vaccines against SARS-CoV-2 is the priority in many pharmaceutical companies and academic organizations all over the world. A variety of SARS-CoV-2 vaccines, such as protein subunit 12 , replicating or non-replicating viral vector 13-15 , inactivated virus 16 , live attenuated virus 17-18 , virus-like particle (VLP) 19-20 , RNA- 21-22 or DNA-based 6, 23-24 vaccines, are currently under development. DNA vaccines have several advantages compared to traditional vaccines, such as protein subunits, peptides, and living/inactivated pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…As antigens, they most commonly carry the hemagglutinin antigen (HA) or the viral neuraminidase. After intramuscular or subcutaneous application in mice, the vaccines have shown to induce immunity against the aforementioned antigens [238]. In the approach to develop a more universal influenza vaccine and eliminate the need of an updated vaccine every year, there is a potential to use a more conserved epitope, such as the stem region of HA with VLPs.…”
Section: Virus-like Particles (Vlps)mentioning
confidence: 99%
“…The plant-produced HA-only VLPs were shown to possess a novel HA glycosylation site belonging to the H3N2 virus 2017 strain whereas the egg-adapted vaccine strain did not contain this new glycosylation site [ 94 ]. These HA-only VLPs were demonstrated to have potent immunogenicity [ 95 , 96 ]. Won et al, 2018 [ 97 ] showed that these HA VLPs could elicit rapid pro-inflammatory cytokine responses from human and mouse dendritic cells in vitro as well as stimulate T cells to produce antigen-specific responses.…”
Section: Influenza Virus Vaccinesmentioning
confidence: 99%